As estruturas semio-narrativas dos contos de fada e maravilhosos no sincretismo verbo-visual do livro infantil - Mabelini, Ecila Lira de Lima (2007)
The research objectified to study in the infantile book contemporary as the classic narratives if they structuralize in a double sincretic expression verb-appearance for its presentation to the reading contemporary. The analysis corpus selected in the set of books of childhood literature, three workmanships: The Cinderela of the dolls, by Ruth Rocha, The problem of the Clóvis, by Eva Furnari and Flicts, by Ziraldo. With the perspective of boarding of the problem guided for the theorist study - methodological of the greimasiana semiotics, the analysis of the gerativo passage of direction, directed toward the examination of the types of sincretics relations was taken in account that constitute the plan of expression of these workmanships. As result the research showed the different mechanisms that can be apprehended in the sincretic organization of the uses of the chosen meaningful systems, verifying as the totality of direction it is constructed by the procedures of joint of the two significant systems. In this way, the observed procedures of sincretization in books show two ways of being: one where verbal and visual they are placed together; in relation, to mean the content and another one where, even so concomitant in one same page, verbal and visual, means separately. As hypothesis the graphical project of the selected workmanships was examined, taking it in terms of the manifest scienter of the citizen of the articulation that organizes the signification, estimated that he has been developed for A.C. of Oliveira. Subsidizing the act to test of the hypothesis it guides, one adopted the theoretical procedures of Jean-Marie Floch of that one and only articulation only conducts the plan of the sincretic expression. Finally, the research also considered as the sincretism of expression is determinative of imitation of projected child in the Brazilian infantile book. Understood the citizen of the articulation as a partnership between enunciator and in agreement enunciatee it has shown the semiotics developed around. the J. Greimas, the result of this research inferred, in the ways of sincretic joint, types of reader-child installed in the literal intrinsic and as these show to assimilate the sincretics mechanisms of the mediatics texts that form its partner-cultural context